2017
DOI: 10.1038/srep39843
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational epimutations induced by multi-generation drought imposition mediate rice plant’s adaptation to drought condition

Abstract: Epigenetic mechanisms are crucial mediators of appropriate plant reactions to adverse environments, but their involvement in long-term adaptation is less clear. Here, we established two rice epimutation accumulation lines by applying drought conditions to 11 successive generations of two rice varieties. We took advantage of recent technical advances to examine the role of DNA methylation variations on rice adaptation to drought stress. We found that multi-generational drought improved the drought adaptability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
118
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 36 publications
(51 reference statements)
7
118
2
Order By: Relevance
“…In particular, DNA methylation is considered a key epigenetic mechanism for which there is now growing evidence (Luo et al, 1996;Boyko and Kovalchuk, 2010;Tricker et al, 2013;Herman and Sultan, 2016;Wibowo et al, 2016;Zheng et al, 2017). The specific contribution of DNA methylation at, or near, protein-coding genes toward basal plant growth and endurance remains unknown, albeit essential for proper development (Finnegan et al, 1996;Henderson and Jacobsen, 2008;Zemach et al, 2013;Yamamuro et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, DNA methylation is considered a key epigenetic mechanism for which there is now growing evidence (Luo et al, 1996;Boyko and Kovalchuk, 2010;Tricker et al, 2013;Herman and Sultan, 2016;Wibowo et al, 2016;Zheng et al, 2017). The specific contribution of DNA methylation at, or near, protein-coding genes toward basal plant growth and endurance remains unknown, albeit essential for proper development (Finnegan et al, 1996;Henderson and Jacobsen, 2008;Zemach et al, 2013;Yamamuro et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence building for the possibility of transgenerational plant stress memory irrespective of chromatin variation (Agrawal, 2002;Rasmann et al, 2012;Murgia et al, 2015;Nosalewicz et al, 2016;Zheng et al, 2017). Indeed, a distinction has been made between transgenerational epigenetic effects, referring to nongenetically determined transgenerational phenotypes, and transgenerational epigenetic inheritance, referring to nongenetically determined transgenerational phenotypes attributable to heritable chromatin modifications (Youngson and Whitelaw, 2008).…”
Section: Transgenerational Inheritance and Methylome Profilingmentioning
confidence: 99%
See 2 more Smart Citations
“…Zheng et al [100] reported that drought adaptability of rice plant improved because of multi-generational drought exposure. They identified appearance of non-random drought-induced epimutations, and a higher proportion of the induced epimutations could maintain the altered DNA methylation level in the subsequent generations.…”
Section: Transgenerational Inheritance Of Epimarksmentioning
confidence: 99%